Conversações com René Girard - Carbone, Silvia Maria (2014)
Conversations with René Girard proposes understanding of the work of Girard in all its complexity. The thesis focuses on analyzing the theory of mimetic desire, the relationship between violence and the sacred, and the need for a scapegoat. Three interwoven, united themes surround all the work of Girard, explained for the first time in the Violence and the Sacred essay considered as one of the pillars of Girardian thought. According to Girard, violence intrinsic to humanity, is the desire to control the violence that establishes the passage of the state of nature to the state of culture. The channeling of violence is vital to the existence of societies - archaic and modern. Girard shows us that the way to control violence is possible only by the institution of the sacred, that is through the atoning sacrifice of the victim. For the author, the desire is always mimetic desire : what is desired by the other subject, which raises the rivalry and consequently the violence that needs to be contained